2016
DOI: 10.1371/journal.pone.0161811
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diverse Efficacy of Salvage Treatment Regimens for Relapsed or Refractory Peripheral T-Cell Lymphoma: A Systematic Review

Abstract: BackgroundThe goal of this study was to perform a systematic review to examine the efficacy and safety of various salvage therapy regimens on patients with relapsed/refractory PTCL.MethodThe electronic searches were performed using PubMed, Cochrane Library, EMBASE, and Web of Science from inception through June 2015, with search terms related to relapsed/refractory PTCL, salvage chemotherapy regimens, and clinical trials. An eligible study met the following inclusion criteria: (1) Patients had refractory or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Peripheral T-cell lymphoma (PTCL) is a highly heterogeneous malignancy accounting for 10%–15% of all non-Hodgkin’s lymphomas in the Western world,1 and its incidence is higher in East Asia 2,3. According to the international T-Cell Lymphoma Project, the major subtypes of PTCL are composed of PTCL not otherwise specified, angioimmunoblastic T-cell lymphoma, and anaplastic large-cell lymphoma 4.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral T-cell lymphoma (PTCL) is a highly heterogeneous malignancy accounting for 10%–15% of all non-Hodgkin’s lymphomas in the Western world,1 and its incidence is higher in East Asia 2,3. According to the international T-Cell Lymphoma Project, the major subtypes of PTCL are composed of PTCL not otherwise specified, angioimmunoblastic T-cell lymphoma, and anaplastic large-cell lymphoma 4.…”
Section: Introductionmentioning
confidence: 99%
“…e possible mechanism is that the drugs disturb the normal axonal transport [48,67,68,[71][72][73][74][75][76][77]. For patients with peripheral neuropathy, CT, biochemical tests, and MRI can be helpful for diagnosis.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…A systematic review published in 2015 identified 14 studies using 12 different salvage approaches and included 618 RR-PTCL patients 23 . The ORR ranged from 22–86%, incorporating a variety of targeted approaches along with single and multi-agent chemotherapies.…”
Section: Salvage Therapy Approachesmentioning
confidence: 99%